Pengaruh Tingkat Hutang, Fee Audit, dan Konsentrasi Pasar Pada Persistensi Laba - Mahendra, Made Edi; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2020)
This study aims to determine whether the level of debt, audit fees, and market concentration affect earnings persistence. This research was conducted on transportation companies listed on the Indonesian stock exchange from 2014 to 2017. The number of samples taken as many as 9 companies using non-probability sampling method with purposive sampling technique. The analysis technique used is multiple linear regression. Based on the results of the analysis found that the level of debt, audit fees, and market concentration has a positive effect on earnings persistence . Keywords: Debt Levels; Audit Fees; Market Concentration; Earnings Persistence.